Oxford handbook of cancer nursing. - Tadman, Mike; Roberts, Dave (Psychiatric nurse); Foulkes, Mark ([New York] : Oxford University Press, 2019)
Taking a systematic approach to the main areas of cancer nursing practice,'Oxford Handbook of Cancer Nursing' covers all aspects of cancer care. It guides the user from pre-diagnosis, through treatment, to issues of advanced disease and palliative care. It includes cancer biology, genetics and treatments, as well as new targeted and complementary therapies.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 10, 2019).
Keywords: Cancer -- Nursing